EVIDENCE OF MAGMA MIXING IN THE 'DALY GAP' OF ALKALINE SUITES: A CASE STUDY FROM THE ENCLAVES OF PANTELLERIA (ITALY) - Ferla P.; Meli C. (My University, 2006)
The island of Pantelleria consists of trachytes, pantellerites and minor mildly alkaline basalts. Rocks of intermediate composition (falling in the so-called 'Daly Gap') such as mugearites, benmoreites and mafic trachytes occur only in the form of enclaves in trachytes and pantellerites inside the main caldera of the island (Caldera 'Cinque Denti'), which collapsed during the 'Green Tuff' ignimbrite eruption at ~50 ka. The enclaves include volcanic, subvolcanic and intrusive rock types. The enclaves in host trachyte contain traces of glass; devitrified glass occurs within enclaves in host pantellerites. Minerals in the enclaves show regular compositional variations with whole-rock silica content. Glass present in the medium-grained samples is interpreted to be the result of incipient melting. The major and trace element compositions of the enclaves show regular and linear variations between an evolved mafic magma (hawaiite) and a felsic end-member similar to the 'Green Tuff' trachyte. Fractional crystallization modelling of compatible and incompatible trace elements (V, Ni, Zr, La, Sm, Lu, Nb, Y, Th) does not reproduce the observed trends. Rocks of intermediate composition within the 'Daly Gap' can be explained only by magma mixing between an already differentiated mafic magma (hawaiite) and an anorthoclase-rich trachytic melt in the lower and higher parts, respectively, of a stratified magmatic chamber. Medium-grained enclaves are interpreted as the result of fragmentation of solidified mixing layers in the roof of the magma chamber during the eruption of the 'Green Tuff', when the collapse of the caldera took place. Diffusion calculations suggest a residence time of <5 days for the enclaves in their host magmas. © 2006 Oxford University Press.
Keywords: DALY GAP; ENCLAVES; MAGMA MIXING; PANTELLERIA